2020
DOI: 10.1002/ccr3.3269
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of olfactory and gustatory dysfunctions in COVID‐19 patients: A case series

Abstract: Although most COVID‐19 patients feel their olfactory function returns to normal, the smell test demonstrates that a mild impairment of the olfactory function may have remained. Therefore, their olfactory function should be evaluated by a smell test.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The UPSIT-TC cutoff scores for an olfactory diagnosis of our study are set based on the validated study in Taiwan, the 'Establishment of olfactory diagnosis for traditional Chinese version of University of Pennsylvania Smell Identi cation Test, 2016' [23], which based on the assessment of the 1440 enrolled subjects, an olfactory diagnosis of UPSIT-TC has been established in relation to gender and age, and the cutoff scores between normosmia and mild hyposmia were established at 29.5 for males aged 20 to 59 years, and the cutoff scores were established at 30.5 for females aged 20 to 59 years [23,24].…”
Section: Secondary Outcome Secondary Outcome Is the Traditional Chinese Version Of The University Of Pennsylvania Smell Identi Cation Tesmentioning
confidence: 99%
“…The UPSIT-TC cutoff scores for an olfactory diagnosis of our study are set based on the validated study in Taiwan, the 'Establishment of olfactory diagnosis for traditional Chinese version of University of Pennsylvania Smell Identi cation Test, 2016' [23], which based on the assessment of the 1440 enrolled subjects, an olfactory diagnosis of UPSIT-TC has been established in relation to gender and age, and the cutoff scores between normosmia and mild hyposmia were established at 29.5 for males aged 20 to 59 years, and the cutoff scores were established at 30.5 for females aged 20 to 59 years [23,24].…”
Section: Secondary Outcome Secondary Outcome Is the Traditional Chinese Version Of The University Of Pennsylvania Smell Identi Cation Tesmentioning
confidence: 99%
“…Moreover, among these and other studies using empirical tests, variable findings have been reported. For example, some studies reported no meaningful association with mean taste test scores, 14 , 15 , 16 whereas others denoted prevalence rates ranging from 12% to 100%. 17 , 18 , 19 , 20 , 21 , 22 , 23 …”
Section: Introductionmentioning
confidence: 99%
“…Moreover, among these and other studies using empirical tests, variable findings have been reported. For example, some studies reported no meaningful association with mean taste test scores, [14][15][16] whereas others denoted prevalence rates ranging from 12% to 100%. [17][18][19][20][21][22][23] This study had 6 main goals: (1) to examine a nationwide sample and evaluate long-term outcomes associated with SARS-CoV-2 using a state-of-the-art, validated 53-item taste test; (2) to compare taste findings with those from a widely used and reliable 40-item olfactory test; (3) to investigate the proportion of individuals who continued to have differing degrees of taste or smell dysfunction a mean of 1 year after their initial infection; (4) to investigate whether COVID-19 was associated with different outcomes in the perception of sweet, sour, bitter, salty, and umami taste qualities in such individuals; (5) to investigate whether age and sex were associated with test findings; and (6) to investigate whether the viral variant prevalent at the time of initial diagnosis was associated with test scores.…”
Section: Introductionmentioning
confidence: 99%